Susceptibility of the hypothalamic-pituitary-thyroid axis to soy isoflavones - Dal Forno, Gonzalo Ogliari (2022)
The increased consumption of soy-based products may be related to health problems, since the content of isoflavones consumed daily starts to represent levels capable of interfering with body homeostasis, acting as a chemical endocrine disruptor. Interference caused by isoflavones in the hypothalamic-pituitary-thyroid (HHT) axis can affect the production of thyroid hormones by interacting with estrogen receptors located in the thyroid, in addition to influencing the action of deiodases for hormone conversion in peripheral tissues. Thus, the objective of this review was to highlight the possible changes caused by the consumption of isoflavones and their impact on the production of thyroid hormones. For this, search platforms such as PubMed, Science Direct and Google Scholar were used. Search filters limiting the year of publication of the articles used as reference were not applied in this research due to the relevance of initial studies that address the relationship between isoflavones/soy and endocrine disruption. Effects of exposure to soy isoflavones (ISOF) on thyroid functions related to subclinical hypothyroidism were evidenced.